Réponses

Meilleure réponse !
2014-03-24T13:03:53+01:00
1) f(x) =( x-3)²-(2x-6)(x+1)
          = x²-6x+9-(2x²+2x-6x-6)
          =x²-6x+9-2x²+4x+6
          =-x²-2x+15

2) f(x) = (x-3)²-(2x-6(x+1)
          = (x-3)²-2(x-3)(x+1)    on factorise par x-3
          = (x-3)[(x-3)-2(x+1)]
          = (x-3)(x-3-2x-2)
          = (x-3)(-x-5)
         
3)
a) c'est l'expression 3 qui convient le mieux 
 f(0) = -3*-5= 15
 f(-1) = (-1-4)(1-5)=-5*-4= 20
 f(3) = (3-3)(-3-5) = 0
 f(-5) = (-5-3)(5-5) = 0

b) c'est la 3 qui convient le mieux
    (x-3)(-x-5) = 0
   x-3 = 0 ou -x-5 = 0
   x = 3 ou x = -5 

c) c'est la 2 qui convient le mieux
   -x²-2x+15 = 15
   -x²-2x = 15-15
   -x(x+2) = 0
     x = 0 ou x+2 = 0
     x = 0  ou x = -2